Modelagem hidrodinâmica e ecológica de reservatório tropical em condição de escassez hídrica - Laura Melo Vieira Soares (2018)
The water quality and the vulnerability reduction to events that pose environmental and health risks are among the main concerns of the management of water resources. Considering that thermal processes in lakes and reservoirs influence the physicochemical characteristics of water and govern the biological dynamics of aquatic organisms, the present study aimed to comprehend the hydrodynamic behavior of a tropical reservoir and its implications on phytoplankton dynamics. In addition, the effects of a drought period were investigated in terms of thermal stratification and mixing of the water column and of biomass and composition of phytoplanktonic organisms. For this purpose, field data was analyzed and mathematical modelling was applied. The hydrodynamic General Lake Model 1D-V (one-dimensional vertical) was coupled with the ecological model Aquatic EcoDynamics (GLM-AED) to simulate the thermal processes and phytoplankton dynamics of Serra Azul Reservoir (MG) from 2009 to 2016. A sensitivity analysis was performed as well as manual calibration and validation of the hydrodynamic model. The results of the sensitivity analysis indicated that the water temperature is more sensitive to changes in wind speed and inflows. The GLM-AED model represented the monomictic behavior of the reservoir and reproduced the biomass and distribution of phytoplankton in the water column. The drought period disrupted the thermal stratification and the reservoir was converted to a polymictic one. Field data indicate the reduction of phytoplankton biomass and a change in its composition during this period. This study shows the use of mathematical modelling as a tool to assist the management of water resources systems. The results point out the need to deal with periods of extreme events for the planning and management of lakes and reservoirs, in order to meet the demand for water quality, as well as to satisfy the ecological and environmental functions of those lentic water bodies